Disruptive innovation and regional entrepreneurship : digital entrepreneurs, sustainability and disruption - Diaz, Jordi; Halkias, Daphne; Harkiolakis, Tatiana (Routledge, 2026)
A new generation of entrepreneurs are leveraging artificial intelligence, data analytics, the Internet of Things (IoT) and other revolutionary technologies for greater social and environmental good. These digital entrepreneurs are developing disruptive solutions to the most pressing sustainability challenges of our time. Yet, behind every case of a successful digital entrepreneur is a wider network of governments, startup incubators and accelerators, incumbent firms, universities and other actors that form a regional entrepreneurial ecosystem.Through in-depth case studies, this book explores how digital entrepreneurs across various geographic regions use disruptive innovation within their regional entrepreneurial ecosystems to leverage digital technologies that create and develop novel business solutions crucial to meeting the United Nations' Sustainable Development Goals. Exploring the perspectives of digital entrepreneurs themselves, each chapter in this book presents a case study that reveals how cultural differences and local socio-economic factors enable digital entrepreneurship driven by disruptive innovation.This book offers insights and recommendations through the stories of digital entrepreneurs across geographic regions for researchers, graduate students, practitioners and public- and private-sector leaders on harnessing the combined power of disruptive innovation and regional entrepreneurial ecosystems to fuel regional economic growth and sustainable development.
Keywords: Disruptive technologies.; Entrepreneurship -- Technological innovations.; Social responsibility of business.; elektronické knihy; electronic books